(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article presents the results of an empirical study of the effect of students psychological anxiety on the success of their education in a higher educational institution, which made it possible to trace changes in the anxiety level of students in everyday life (personal anxiety) and in the situation of the exam (situational anxiety) and to reveal a number of patterns of the influence of anxiety on student performance university. It is established that the psychological state of anxiety, being a subjective factor, significantly affects the success and productivity of the activity, especially the educational one.